2006
DOI: 10.1245/aso.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Location and Extension of Portal Vein Tumor Thrombus on Long-Term Outcomes of Surgical Treatment for Hepatocellular Carcinoma

Abstract: Liver resection with thrombectomy yielded better outcomes in the HCC patients with PVTT confined to the first or second branch of the main portal vein compared with PVTT extending into the main portal vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
116
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 24 publications
4
116
0
4
Order By: Relevance
“…In our study, after HR, there was one postoperative in-hospital death caused by postoperative liver failure (0.5%), and the major complication rate was 4.0% (8 of 201), our results were similar to the studies reported previously. [13][14][15][16][17][18][19][20][21][22] Therefore, HR is still a safe treatment for HCC with PVTT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, after HR, there was one postoperative in-hospital death caused by postoperative liver failure (0.5%), and the major complication rate was 4.0% (8 of 201), our results were similar to the studies reported previously. [13][14][15][16][17][18][19][20][21][22] Therefore, HR is still a safe treatment for HCC with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] To improve on the results of treatment of HCC with PVTT, attempts have been made to perform HR for these patients. [13][14][15][16][17][18][19][20][21][22] HCC with PVTT remains a contraindication to liver transplantation because of the high rate of tumor recurrence, and because of the severe shortage of donor organs. HR remains the only therapeutic option that may still offer a chance of cure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC has become the fifth most prevalent malignancy worldwide and the third leading cause of cancer-related death, most importantly, the incidence of HCC is increasing [1,2] , and 82% of cases are in developing countries, with 55% in China alone [3] . Invasion and metastasis are two fundamental properties, which determine the prognosis of the HCC patients [4,5] . Many signaling pathways are thought to be involved in the development and invasion of HCC, including the MAPK pathway [6,7] , phosphatidylinositol-3 kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway [8][9][10] , the wnt/beta-catenin pathway [9,11] , hepatocyte growth factor/c-MET pathway [12,13] , hedgehog (Hh) signaling pathway, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and colleagues [14] surgically treated 438 patients with HCC and PV invasion: 286 of them had PVTT not extended into the MPV and were treated with hepatic resection only, while 152 patients had PVTT extended into the PV and were treated with hepatic resection and thrombectomy. Six months recurrence rates were 11.3% in the first group and 76.9% in the second group.…”
Section: Discussionmentioning
confidence: 99%